Low inhibitory effect of ammonia on the nitrogen-fixing activity of a sludge enriched with nitrogen-fixing bacteria. (June 2021) - Ospina-Betancourth, Carolina; Acharya, Kishor; Sanabria, Janeth; Curtis, Thomas P.
Abstract: In principle, high carbon to nitrogen wastes can be used to produce nitrogen-fixing bacteria and thus create a potential biofertiliser. In practice biological nitrogen fixation can be inhibited by the presence of ammonia. We wish to know what concentrations of ammonia are inhibitory. We therefore "challenged" sludge from reactors fed with high carbon to nitrogen wastewater with different ammonia concentrations and measured the effect on nitrogen fixation rates. The sludge was resistant to inhibition by ammonia with a half maximal inhibitory concentration (IC50 ) of 70.2 mg of NH4 + L −1 . Moreover, the presence of modest amounts of ammonium in the reactors did not affect the capacity of the biomass to reduce the organic matter contained in the wastewater. We conclude that high carbon to nitrogen wastes can be used to generate a potential fertiliser that could work in the presence of high levels of ammonia contamination. Graphical abstract: Unlabelled Image Highlights: Biological nitrogen fixation (BNF) and ammonia uptake were assessed as concurrent. BNF was reduced by 83% when treating wastewater containing up to 78 mg of N L −1 . The nitrogen present in the system did not affect its organic carbon removal rate. BNF may occur in typical municipal wastewater treatment systems.